Possibilities of using rooted cuttings of European beech (Fagus sylvatica L.) for stabilisation of forest ecosystems - A. Jurásek (Journal of Forest Science, 2007)
Vegetative propagation of forest tree species is of great importance not only for breeding programmes but also for the conservation of valuable populations of tree species. Important is also a possibility of improving the genetic quality of established stands. Beech is a tree species that can substantially increase the stability of forest ecosystems. Minimal information is available about the ontogenesis of rooted cuttings of beech in forest stands for the time being. In our experiments that were gradually established since 1993 we acquired the first significant results of the evaluation of health status, phenological phenomena and growth of these plants. Our findings indicate that it is possible to use rooted cuttings as an element stabilising man-made forest stands including the transferred genetic quality. The evaluation of the 2nd generation rooted cuttings of beech also provided positive results.